PENERAPAN ALGORITMA FLOYD WARSHALL UNTUK MENENTUKAN JALUR WIFI TERPENDEK DI STUDENTCOMP - Agus Hening Triwasono; Ida Widaningrum; Khoiru Nurfitri (KOMPUTEK, 2021)
Studentcomp is one of the service providers engaged in the IT field. Studentcomp is located at Jl. Raya Lekong, Gandukepuh, Sukorejo, Ponorogo. Studentcomp offers several services, one of which is wireless wifi service. In these services, there are often obstacles in terms of billing to the customer's place. this often makes the billing department wrong in determining which path to take and which customers have not paid and which have paid. then a system is made that can help the employees of the wifi billing department in determining the shortest path to the customer's place using the floyd warshall algorithm. the floyd warshall algorithm itself uses a dynamic system so that it guarantees in terms of determining the optimum solution in terms of determining the shortest path. The results obtained by applying this algorithm to the system are assisting employees in determining the shortest path that must be taken to the customer's place and being able to find out which customers have or have not paid.